Faktor-faktor yang Mempengaruh SIndrom Pre-Menopuuse di Desa Senon, Kecamatan Kemangkon, Kabupaten Purbalingga - Sejati, Waluyo; Handoyo,; Swasti, Keksi Girindra (Jurusan Keperawatan FIKES UNSOED, 2008)
Premenopause syndrom is the period 4-5 years before menopause. Study was held in Holland show that the woman in 42-62 years old are 17% have hot flushing complaint, and 40% have a bad menstrual cycle. This condition will increase until 60% when 1-2 years before menopause. The aim of this study is to know the influences of physical factors, psyche factors, habit factors, and knowledge factors and also a dominant influence factor to the premenopause syndrom in Senon, Kemangkon, Purbalingga. This is analysis study that use corelation study (Ãâ€¡2 analysis) and continued with logistic regretion analysis. The subjects of this study are 30 respondents who included in inclusion criterias. From 30 respondents, there are 23 respondents who have premenopause syndrom, 22 respondents who have physical factors, 13 respondents who have psyche factors, 15 respondents who have habit factors, and eight respondents have a good knowledge about premenopause syndrom. From four factors, there are three factors (physical factors, psyche factors and knowledge factors) that have significant influences to the premenopause syndrom, with significant value for each factors are p<0,0001; p<0,038 dan p<0,025. Habit factors not give a significant influence to the premenopause syndrom (p<0,084). Based on logistic regretion analysis, we know that there is no dominant influence factor to the premenopause syndrom in Senon, Kemangkon, Purbalingga. Physical factors, psychological factors and knowledge factors have significant influences to the premenopause syndrom. However, habitual factors did not give a significant influence to the premenopause syndrom. There is no dominant influence factor to the premenopause syndrom at Senon, Kemangkon, Purbalingga